2010
DOI: 10.1002/mpr.299
|View full text |Cite
|
Sign up to set email alerts
|

Measuring disability across cultures — the psychometric properties of the WHODAS II in older people from seven low‐ and middle‐income countries. The 10/66 Dementia Research Group population‐based survey

Abstract: We evaluated the psychometric properties of the 12-item interviewer-administered screener version of the World Health Organization Disability Assessment Schedule – version II (WHODAS II) among older people living in seven low- and middle-income countries. Principal component analysis (PCA), confirmatory factor analysis (CFA) and Mokken analyses were carried out to test for unidimensionality, hierarchical structure, and measurement invariance across 10/66 Dementia Research Group sites.PCA generated a one-factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
98
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 34 publications
5
98
1
3
Order By: Relevance
“…The confirmation of unidimensionality is consistent with Luciano et al [13] who analysed data of Spanish patients with major depression using exploratory principal component and subsequent confirmatory factor analysis. Sousa et al [12] examined unidimensionality of the WHODAS 2.0 in elderly people living in seven low-and middle-income countries and showed that principle component analysis gave rise to a one-factor solution in most countries. In the study from Andrews et al [11] a second-order one-factor solution with six first-order factors was the best-fitting model for the Australian general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The confirmation of unidimensionality is consistent with Luciano et al [13] who analysed data of Spanish patients with major depression using exploratory principal component and subsequent confirmatory factor analysis. Sousa et al [12] examined unidimensionality of the WHODAS 2.0 in elderly people living in seven low-and middle-income countries and showed that principle component analysis gave rise to a one-factor solution in most countries. In the study from Andrews et al [11] a second-order one-factor solution with six first-order factors was the best-fitting model for the Australian general population.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in contrast to the 36-item WHODAS, for the 12-item form studies on its psychometric properties are scarce so far. The available studies are limited to the general population [11], older people [12], and patients with depression [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The self-reported measures were stroke and having three or more limiting physical impairments from the following list : arthritis or rheumatism, eyesight problems, hearing difficulty or deafness, persistent cough, breathlessness, difficulty breathing or asthma, high blood pressure, heart trouble or angina, stomach or intestine problems, faints or blackouts, paralysis, weakness or loss of one leg or arm, skin disorders such as pressure sores, leg ulcers or severe burns (Sousa et al 2010).…”
Section: Other Measuresmentioning
confidence: 99%
“…This scale was developed by the World Health Organization as a cross-cultural and culture-fair assessment tool to use in epidemiological studies. Its psychometric properties have recently been assessed (Sousa et al 2010).…”
Section: Other Measuresmentioning
confidence: 99%
“…The pattern of correlations he found did not offer support for the multidimensionality of the SGRQ. By using a combination of appropriate exploratory and confirmatory, parametric and non-parametric, IRT and factor analytic models, as suggested by several researchers [e.g., 16,18,29,[59][60][61][62], we managed to obtain a comprehensive picture of the psychometric properties of the SGRQ. The results from the MSA, MIRT and confirmatory bifactor analysis suggest that (a shorter version of) the SGRQ can be used to calculate a total (unidimensional) score.…”
Section: Discussionmentioning
confidence: 99%